THE IMPACT OF ORGANIZATIONAL DESIGN ON EMPLOYEE PERFORMANCE AND JOB SATISFACTION - Hemwani, Ms. Ritika; Husaini, Dr. Farida (The journal of contemporary issues in business and government, 2023)
This paper examines how organizational design impacts employee performance and job satisfaction. It covers the structure, processes, and systems that help organizations achieve goals. Employee performance involves productivity, engagement, decision-making, and continuous learning. Job satisfaction is influenced by communication, collaboration, and office design. Well-designed structures, effective communication and collaboration foster positive relationships, engagement, and problem-solving. It emphasizes recognizing the link between design and knowledge management for success. In conclusion, organizational design significantly shapes employee performance and job satisfaction.